Advances in Research on the Release of von Willebrand Factor from Endothelial Cells through the Membrane Attack Complex C5b-9 in Sepsis - Liu Y; Zhao W; Huang Q; Wan L; Ren Z; Zhang B; Han C; Yang J; Zhang H; Zhang J (Journal of Inflammation Research, 2025)
Yi Liu,1 Weili Zhao,2 Qingqing Huang,1 Linjun Wan,1 Zongfang Ren,1 Bangting Zhang,1 Chen Han,1 Jin Yang,1 Haoling Zhang,3 Jingjing Zhang4,5 1Department of Critical Care Medicine, The Second Affiliated Hospital of Kunming Medical University, Kunming, 650101, People’s Republic of China; 2Laboratory Department, The Second Affiliated Hospital of Kunming Medical University, Kunming, 650101, People’s Republic of China; 3Department of Biomedical Science, Advanced Medical and Dental Institute, University Sains Malaysia, Penang, 13200, Malaysia; 4Fuwai Yunnan Hospital, Chinese Academy Medical Sciences, Kunming, 650000, People’s Republic of China; 5Affiliated Cardiovascular Hospital of Kunming Medical University, Kunming, 650000, People’s Republic of ChinaCorrespondence: Jingjing Zhang, Email zhangjingjing1@kmmu.edu.cn Haoling Zhang, Email zhaohaoling@student.usm.myAbstract: Sepsis, a lethal organ dysfunction syndrome driven by aberrant host responses to infection, intertwines excessive inflammatory responses and dysregulated coagulation processes in its pathophysiology. Emerging research reveals the complement terminal membrane attack complex C5b-9 orchestrates ultralarge von Willebrand factor (ULVWF) release from vascular endothelial cells (ECs) through multifaceted mechanisms: C5b-9 compromises EC membrane integrity, activates calcium influx cascades, and provokes NLRP3 inflammasome signaling, triggering massive exocytosis of ULVWF stored within Weibel-Palade bodies (WPBs). When ADAMTS13 activity falters, undegraded ULVWF complexes with platelets to spawn microthrombi, precipitating microvascular occlusion and multiorgan collapse. Strikingly, elevated plasma von Willebrand factor (vWF) antigen levels in sepsis patients correlate robustly with endothelial injury, thrombocytopenia, and mortality—underscoring C5b-9-driven vWF release as a linchpin of septic coagulopathy. Current therapeutic strategies targeting these pathways, including recombinant ADAMTS13 (rhADAMTS13), N-acetylcysteine (NAC), and complement inhibitors like eculizumab, face limitations in clinical translation, necessitating further validation of their efficacy. Additionally, investigating complement regulatory molecules such as CD59 may unlock novel therapeutic avenues. Deciphering the intricate interplay within the C5b-9-vWF axis and advancing precision therapies hold transformative potential for ameliorating sepsis outcomes.Keywords: sepsis, C5b-9 complex, von Willebrand factor, platelet-ULVWF microthrombus, endothelial dysfunction